Prevalence and determinants of active trachoma among preschool-aged children in Dembia District, Northwest Ethiopia - Ayanaw Tsega Ferede; Abel Fekadu Dadi; Amare Tariku; Akilew Awoke Adane (BMC, 2017)
Abstract Background Trachoma is an infectious eye disease caused by Chlamydia trachomatis, which is the leading infectious cause of blindness worldwide. In areas where trachoma is endemic, active trachoma is common among preschool-aged children, with varying magnitude. This study aimed to estimate the prevalence of active trachoma and associated risk factors among preschool-aged children in Dembia District, northwest Ethiopia. Methods A community-based cross-sectional survey was conducted among preschool-aged children of northwest Ethiopia. Multistage systematic random sampling was used to select 695 subjects. Trained clinical optometrists subjected each child to an ocular examination and assessed the presence of active trachoma. Face to face interview using pretested and structured questionnaire were conducted to collect data on possible risk factors. Trachoma cases were graded following a World Health Organization simplified grading scheme. All statistical analysis was carried out using the SPSS software version 20. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were used to identify factors associated with active trachoma. Results Of the 681 preschool-aged children studied, 18% (95% CI: 15.4% - 21.1%) had a prevalence of active trachoma. Children who had clean faces (absence of nasal and ocular discharges) had a lower chance of having active trachoma [aOR = 0.55, 95% CI: 0.37 - 0.82]. The odds of having active trachoma decreased with an increase in the distance to a water point [aOR = 0.51, 95% CI: 0.33 - 0.78]. Similarly, no or poor utilization of liquid waste disposal in the child's household was associated with an increased chance of having active trachoma [aOR = 3.83, 95% CI: 1.26 - 11.61]. Conclusion The prevalence of active trachoma in these preschool-aged children was found to be high and needs special interventions that focus on educating families about proper face washing, liquid waste disposal, and improving safe water supply near the households.